Comprehensive analysis of α2,3-sialyltransferases as prognostic biomarkers and immunotherapy targets in kidney renal clear cell carcinoma - Yuli Jian; Kangkang Yang; Jinjing Li; Ling Tang; Guang Zeng; Xiaoxin Sun; Xiao Yu; Abdullah Al-danakh; Qiwei Chen; Deyong Yang; Shujing Wang (Cancer Cell International)
Abstract Kidney renal clear cell carcinoma (KIRC), a therapy-resistant aggressive kidney cancer, exhibits resistance to immune checkpoint inhibitors. Altered sialylation is involved in tumor development, affecting immune microenvironment dynamics. In the study, through systematic bioinformatics analysis and experimental verification, we demonstrated that ST3Gal5 expression was elevated in tumor tissues of KIRC patients, correlating with poor prognosis, and ST3Gal1 was downregulated and associated with a better prognosis. Immunohistochemistry analysis confirmed the expression patterns of ST3Gal1 and ST3Gal5 in 30 KIRC patients. Furthermore, KIRC patients were stratified into two clusters based on ST3Gal1 and ST3Gal5 levels using consensus clustering to investigate their roles in KIRC tumorigenesis, immune characteristics and treatment sensitivity. KIRC patients in Cluster 2, characterized by increased ST3Gal5 and downregulated ST3Gal1 expression, exhibited increased expression of immune checkpoints, immune cell infiltration, immune escape scores, and worse prognosis. Knockdown of ST3Gal5 in KIRC cell lines (786-O and 769-P) resulted in reduced tumor proliferation, migration, and invasion in vivo and in vitro. Together, the dysregulation of sialyltransferases (ST3Gal1 and ST3Gal5) in KIRC influences tumorigenesis and immune responses. These findings underscore the potential of ST3Gal1 and ST3Gal5 as prognostic factors and immunotherapy targets for KIRC.